2020
DOI: 10.1016/j.nicl.2020.102426
|View full text |Cite
|
Sign up to set email alerts
|

Behavioral and electrophysiological effects of network-based frontoparietal tDCS in patients with severe brain injury: A randomized controlled trial

Abstract: Highlights Behavioral and EEG effects of multifocal frontoparietal tDCS are investigated in patients with severe brain injury. No behavioral treatment effect was identified at the group level while EEG complexity increased in low frequency bands. Electrophysiological changes were not translated into behavioral changes at the group level.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
58
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 33 publications
(59 citation statements)
references
References 41 publications
1
58
0
Order By: Relevance
“…In another study, active tDCS alleviated tinnitus and this negatively correlated with baseline EEG high-frequency band power (eyes open mainly, and at specific electrodes) [22]. Recently, bilateral fronto-parietal tDCS in severely brain injured patients with prolonged disorders of consciousness showed no behavioral effects after one session; however, they did find a treatment effect on Lempel-Ziv-Welch complexity in the theta and delta bands (LZW) showcasing tDCS' neurophysiological effects even in the absence of behavioral changes in challenging populations [23]. The LZW algorithm has been previously correlated with sleep and levels of consciousness and is considered to depict the "randomness" and integrity of neural signals and connectivity respectively [23]- [28].…”
Section: [Insert Figure 5 Here]mentioning
confidence: 99%
See 1 more Smart Citation
“…In another study, active tDCS alleviated tinnitus and this negatively correlated with baseline EEG high-frequency band power (eyes open mainly, and at specific electrodes) [22]. Recently, bilateral fronto-parietal tDCS in severely brain injured patients with prolonged disorders of consciousness showed no behavioral effects after one session; however, they did find a treatment effect on Lempel-Ziv-Welch complexity in the theta and delta bands (LZW) showcasing tDCS' neurophysiological effects even in the absence of behavioral changes in challenging populations [23]. The LZW algorithm has been previously correlated with sleep and levels of consciousness and is considered to depict the "randomness" and integrity of neural signals and connectivity respectively [23]- [28].…”
Section: [Insert Figure 5 Here]mentioning
confidence: 99%
“…Recently, bilateral fronto-parietal tDCS in severely brain injured patients with prolonged disorders of consciousness showed no behavioral effects after one session; however, they did find a treatment effect on Lempel-Ziv-Welch complexity in the theta and delta bands (LZW) showcasing tDCS' neurophysiological effects even in the absence of behavioral changes in challenging populations [23]. The LZW algorithm has been previously correlated with sleep and levels of consciousness and is considered to depict the "randomness" and integrity of neural signals and connectivity respectively [23]- [28]. Finally, one study used 44 participants' individual MRI-based models (and the finite-element method) to compare different tDCS electrode sizes and configurations; they confirmed that a smaller electrode size can increase electric field focality, but also increases inter-subject variability in electric fields [29].…”
Section: [Insert Figure 5 Here]mentioning
confidence: 99%
“…This is currently the gold-standard for diagnosis in PDOC. Out of these 19 studies, 10 did not report significant changes in behavioral responsiveness at the group level following tDCS ( 28 , 32 , 34 38 , 40 42 ). Interestingly however, eight of these reported significant EEG changes (see section below).…”
Section: Clinical Effects Of Tdcs In Pdocmentioning
confidence: 98%
“…A total of 20 studies have investigated the effects of tDCS stimulation in the level of consciousness of PDOC patients. Among these, nine considered effects of a single-session of tDCS ( 23 , 25 , 32 38 ) and the remaining 11 involved multiple tDCS sessions ( 5 20 , 24 , 26 30 , 39 43 ) (see Tables 1 , 2 ). While the majority of the studies used a double-blind, sham-controlled randomized crossover design, a small number used (double-blind, sham-controlled) randomized non-crossover designs ( 27 , 42 ), open-label sham-controlled designs ( 24 , 34 ), or open-label without a sham condition ( 29 , 30 , 43 ).…”
Section: Clinical Effects Of Tdcs In Pdocmentioning
confidence: 99%
See 1 more Smart Citation